Environmental Cycles, Melatonin, and Circadian Control of Stress Response in Fish - Sánchez-Vázquez, Francisco Javier; López-Olmeda, Jose Fernando; Vera, Luisa Maria; Migaud, Herve; López-Patiño, Marcos Antonio; Míguez, Jesús M. (Frontiers in Endocrinology, 2019)
Fish have evolved a biological clock to cope with environmental cycles, so they display circadian rhythms in most physiological functions including stress response. Photoperiodic information is transduced by the pineal organ into a rhythmic secretion of melatonin, which is released into the blood circulation with high concentrations at night and low during the day. Melatonin rhythms are under the control of circadian clocks in most fish (except salmonids), and it is considered as an important output of the circadian system, modulating most daily behavioural and physiological rhythms. Many factors display daily rhythms along the hypothalamus-pituitary-interrenal (HPI) axis that controls stress response in fish, including corticotropin-releasing hormone (Crh) and its binding protein (Crhbp), proopiomelanocortin A and B (Pomca and Pomcb), and plasma cortisol, glucose, and lactate. Many of these circadian rhythms are under the control of endogenous molecular clocks, which consist of self-sustained transcriptional-translational feedback loops involving the rhythmic expression of circadian clock genes (clock, bmal, per and cry) which persists under constant light or darkness. Exposing fish to a stressor can result in altered rhythms of most stress indicators, such as cortisol, glucose and lactate among others, as well as daily rhythms of most behavioral and physiological functions. In addition, crh and pomca expression profiles can be affected by other factors such as light spectrum, which influence the expression profile of growth-related (igf1a, igf2a) genes. Additionally, the daily cycle of water temperature (warmer at day and cooler at night) is another factor that has to be considered. The response to an acute stressor depends also on the time of the day when the stress occurs: nocturnal species show higher responses when stressed during day time, whereas diurnal fish respond stronger at night. Melatonin administration in fish has sedative effects with a reduction in locomotor activity and cortisol levels, as well as reduced liver glycogen and dopaminergic and serotonergic activities within the hypothalamus. In this paper, we are reviewing the role of environmental cycles and biological clocks on the entrainment of daily rhythms in the HPI axis and stress responses in fish.